Linear and rationally designed stapled peptides abrogate TLR4 pathway and relieve inflammatory symptoms in rheumatoid arthritis rat model - Achek, Asma; Shah, Masaud; Seo, Ji Young; Kwon, Hyuk Kwon; Gui, Xiangai; Shin, Hyeon Jun; Cho, Eun Young; Lee, Byeong Sung; Kim, Dong Jin; Lee, Sang Ho; Yoo, Tae Hyeon; Kim, Moon Suk; et al. (Journal of Medicinal Chemistry, 2019)
A mounting evidence exists for the despicable role of the aberrant immune response in the pathogenesis of rheumatoid arthritis (RA), where toll-like receptor 4 (TLR4) can activate synovial fibroblasts that lead to the chronic inflammation and joint destruction, thus making TLR4 a potent drug target in RA. We report that novel TLR4-antagonizing peptide, PIP2, inhibits the induction of inflammatory biomarkers in vitro as well as in vivo. Systemically, PIP2 inhibits the lipopolysaccharide (LPS)-elicited TNF-α, IL-6, and IL-12p40 in a mouse model. The rationally designed cyclic derivative, cPIP2, is capable of inhibiting LPS-induced proinflammatory cytokines at significantly lower concentration as compared to PIP2 (PIP2 IC50 = 20 μM, cPIP2 IC50 = 5 μM). Finally, cPIP2 was able to relieve the inflammatory symptoms and synovial tissue destruction in the RA rat model. Cumulatively, these data suggest that PIP2 and cPIP2 hold strong promise for the development of peptide-based immunotherapeutics that could be of great value in curbing TLR-related immune complications including RA.
Keywords: Animals; Anti-Inflammatory Agents; Arthritis, Rheumatoid; Drug Design; Lipopolysaccharides; Male; Mice; Peptides; Rats; Rats, Inbred Lew; RAW 264.7 Cells; Signal Transduction; Toll-Like Receptor 4; Tumor Necrosis Factor-alpha